The Protective Effects of Three Polysaccharides From Abrus cantoniensis Against Cyclophosphamide-Induced Immunosuppression and Oxidative Damage - Qu, Dongshuai; Hu, Hongjie; Lian, Shuaitao; Sun, Wenjing; Si, Hongbin (Frontiers in Veterinary Science, 2022)
This study was designed to systematically elucidate the immunomodulatory and antioxidant effect of three polysaccharide fractions (ACP60, ACP80 and ACPt2) from Abrus cantoniensis (A. cantoniensis) on CTX-induced immunosuppressive mice. The experimental mice were divided into 12 groups, then modeled and administrated with different doses of three polysaccharides (50, 150, 300 mg/kg/d) by gavage. The results showed that ACP could markedly recover the CTX-induced decline in immune organ and hemocytes indexes and promote proliferation of splenocytes, earlap swelling rate, secretion of cytokines (TNF-α, IFN-γ, IL-1β, IL-6) and immunoglobulin (Ig-M and Ig-G). Additionally, ACP improved the enzymatic activities of T-SOD and GSH-PX were greatly, while the level of MDA was significantly decreased in liver. In particular, ACPt2 had higher immunomodulatory and antioxidant activity than ACP60 and ACP80. Based on the presentfindings, ACP could be utilized as an efficacious candidate for immunomodulators and antioxidants, which provide a new application prospect in the food and pharmaceutical industries.